Legal Protection For Consumers In Electronic Transactions - Manuel Lambi; Carina Budi Siswani (Eduvest - Journal of Universal Studies, 2024)
The development of e-commerce transactions also provides opportunities and challenges for consumers. The opportunity for consumers is that they can easily and quickly get the goods or services they need. However, the challenge for consumers is the risk of fraud or violation of consumer rights in e-commerce transactions. The aim of this research is to determine legal protection regulations and their implementation for consumers in e-commerce transactions in Indonesia. This research uses legal research methods with a normative juridical approach. The data collection technique in this research is literature study. The data that has been collected is then analyzed qualitatively by understanding and interpreting the data in depth. The research results show that aspects of legal protection for consumers in buying and selling transactions via electronic media are regulated in several laws, namely Law Number 8 of 1999 concerning Consumer Protection, Law Number 7 of 2014 concerning Trade, and Law Number 19 of 2016 concerning Changes. Implementation of this Law is carried out through several steps, including the establishment of special regulations detailing consumer rights and obligations in electronic transactions. Apart from that, implementation also involves active law enforcement to deal with violations of consumer protection provisions as well as efforts to increase consumer awareness through various education and information programs.